2007
DOI: 10.5650/jos.56.163
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Washing Efficiency for Solid Particle Soil

Abstract: In a previous study, statistical method using two distributions was applied to analyze detergency of oily soil. The method uses statistical distributions of detergent power and adhesive force of soil. In this paper, this method was applied to an analysis of detergency of solid particles. Soiled cotton cloth was prepared with red iron oxide dispersion liquid in Terg-O-Tometer. Four-time consecutive washings tests were conducted with dodecyl sulfuric acid sodium salt (SDS) and alcohol ethoxylate (AE) aqueous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Ferric oxide has a red color, so detergency is easily analyzed by the widely used refraction method [20][21][22][23][24]. Kaolinite has a white color, so refraction is not effective for measuring residual soil.…”
Section: Comparison Between Quantitative and Qualitative Analysis Formentioning
confidence: 99%
See 1 more Smart Citation
“…Ferric oxide has a red color, so detergency is easily analyzed by the widely used refraction method [20][21][22][23][24]. Kaolinite has a white color, so refraction is not effective for measuring residual soil.…”
Section: Comparison Between Quantitative and Qualitative Analysis Formentioning
confidence: 99%
“…It was concluded that the shift in the point of zero charge of the Fe 2 O 3 particles to a lower pH by the adsorption of anionic surfactant promoted the detachment of the particles from the fabric surface and prevented the re-adhesion of detached particles onto the fabric. The statistical analysis of washing efficiency of solid particulate soil (ferric oxide) was studied by Ishikawa et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…In those studies, oily soil and solid particle soil were washed with surfactant solution, and the results showed that experimental removal efficiencies corresponds to predicted removal efficiencies which were calculated from washing simulation using distributions of detergent power 1,2) . Practical soil component is mostly a mixture of solid particles, oily soil, protein, etc.…”
Section: Introductionmentioning
confidence: 85%
“…In the probability density functional method [35][36][37][38][39], the adhesion force of soil and the removal force of soil are assumed to be in accordance with a normal distribution, and the cleaning efficiency is determined based on both distributions. Further assumptions are that the adhesion force of soil is in accordance with a normal distribution with an average value of 0 and a standard deviation of 1 (Eq 3), and the cleaning power is in accordance with a normal distribution with an average value of μ rl and a standard deviation of σ rl (Eq 4).…”
Section: Methodsmentioning
confidence: 99%
“…An attempt was made to apply the probability density function to the detergency evaluation. The washing results of an oily dye stain [35], iron oxide particle dirt [36], and commercially available washing test cloth soiled with a mixed stain [37] were analyzed with respect to two parameters of the probability density functional method, the mean μ rl and standard deviation σ rl of the removal load distribution, assuming that the cleaning power follows a normal distribution. It was recently demonstrated that one of the two parameters (σ rl ) is related to the soil type [38] and the soil removal mechanism [39].…”
Section: Introductionmentioning
confidence: 99%